PEMBELAJARAN ETNOMATEMATIKA PADA PERMAINAN TRADISIONAL JAMURAN - Intan Novita Sari; Arissona Dia Indah Sari (Cahaya Ilmu Bangsa Institute, 2024)
Ethnomath is a study that studies the way that people in certain cultures understand, express, and use its cultural concepts and practices that researchers describe as mathematical. The study aims to conduct literature review relating to ethnomath exploration in traditional games and to be able to know and understand the role it plays in raising children's capacities and interests in mathematics. They are also useful asa means of preserving traditional games and inspiring outdoor learning activities for elementary school teachers. The study method used in this study is the SLR (literature review) method. Data collection is done by documenting all articles that have similar research on research reports.